Answer:
All roots of the given function are, 2 , 3 and 4
Explanation:
Given the function f(x) =
![x^3-9x^2+26x-24](https://img.qammunity.org/2019/formulas/mathematics/middle-school/g13qlnoqwatzg2mzeol0we0z3rkq9rjw3j.png)
Also, it given that x=2 is a root of the function f(x).
So, (x-2) is a factor of f(x).
Remainder theorem states that if a function is divided by (x-a), then the remainder is equal to f(a). If a function f(a) is equal to 0, therefore a is the root of the function.
We use synthetic method to divide f(x) by (x-2) as also shown in figure below;
![f(x) = (x-2)(x^2-7x+12)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/pacdvm6nro5zxpzz9e41sv738bmq8t8msg.png)
![f(x)=(x-2)(x^2-3x-4x-12)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vsgv70hqyg94c5j3a85xemm1a45et0y4rl.png)
![f(x) = (x-2)(x(x-3)-4(x-3))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/n2jhmmtyu23pc1z73ct8duymw4q7rb2ybk.png)
![f(x) = (x-2)(x-3)(x-4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ax4bny5xs4e3hmybyradh29msukanksryh.png)
To find the roots of the function f(x) equate f(x) = 0.
we have;
![(x-2)(x-3)(x-4) =0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5ir1lg3f7arrptsljux5u9sklc6o4tg0ei.png)
By zero product property states that if ab = 0, then either a = 0 or b = 0, or both a and b are 0.
x = 2 , 3 and 4.
Therefore, the roots of the given functions are; 2 , 3 and 4.